Hypovitaminosis D and Low Urinary Tract Symptoms in a Female Population. (May 2014) - Foti, D.; Greco, M.; Cantiello, F.; Damiano, R.; Gulletta, E.; Pujia, A.; Montalcini, T.
An increasing number of studies have suggested a key role for low levels of vitamin D in the development of several chronic diseases and bacterial infections. In particular, its role in acute respiratory infection has been clarified, while the potential role of vitamin D for susceptibility to urinary tract infections still remains unexplored. Since the typical symptoms associated with urinary infections or with other conditions, like overactive bladder, include dysuria, urgency and frequency, the aim of this study was to investigate the association between these symptoms and vitamin D status. We conducted a retrospective study on 233 women who, in the previous year, had their serum levels of vitamin D measured. The subjects were queried about the presence of urinary symptoms and their frequency over the previous year. Women with low serum levels of vitamin D had a higher prevalence of symptoms than those with normal levels of vitamin D (p<0.001). In particular, women who reported high frequency of symptoms had a mean vitamin D level of ∼ 27 ng/mL, those with low frequency had a mean vitamin D level of ∼ 24 ng/mL, while asymptomatic women had mean levels of ∼ 37 ng/mL (p=0.004 among group). In this study hypovitaminosis D is associated with urinary symptoms in a population of women, and it may suggest a key role of this vitamin in the development of infections or other conditions affecting the urinary tract.